Comparison of outcomes after umbilical cord blood and unmanipulated haploidentical hematopoietic stem cell transplantation in children with high‐risk acute lymphoblastic leukemia. Issue 9 (15th July 2016) - Mo, Xiao‐Dong; Tang, Bao‐Lin; Zhang, Xiao‐Hui; Zheng, Chang‐Cheng; Xu, Lan‐Ping; Zhu, Xiao‐Yu; Wang, Yu; Liu, Hui‐Lan; Yan, Chen‐Hua; Chu, Xian‐Deng; Chen, Huan; Geng, Liang‐Quan; et al.
Abstract : Allogeneic hematopoietic stem cell transplantation (HSCT) is an effective therapy for children with high‐risk acute lymphoblastic leukemia (ALL). Human leukocyte antigen (HLA)‐haploidentical HSCT (haplo‐HSCT) or umbilical cord blood transplantation (UCBT) are both important alternative sources of stem cells for those without an HLA‐identical sibling donor or unrelated matched donor. We aimed to compare the therapeutic effects of single UCBT and unmanipulated haplo‐HSCT in high‐risk ALL children ( n = 129). Hematopoietic recovery was significantly faster in haplo‐HSCT recipients than in UCBT recipients. The 2‐year cumulative incidences of relapse in the haplo‐HSCT and UCBT groups were 16.1% and 24.1%, respectively ( p = 0.169). The 2‐year cumulative incidences of non‐relapse mortality in the haplo‐HSCT and UCBT groups were 12.8% and 18.8%, respectively ( p = 0.277). The 2‐year probabilities of overall survival in the haplo‐HSCT and UCBT groups were 82.0% and 69.6%, respectively ( p = 0.071), and the 2‐year probability of disease‐free survival in the haplo‐HSCT group was higher than in the UCBT group (71.0% vs. 57.2%, p = 0.040). However, several variables (such as leukocyte count and cytogenetics at diagnosis) were different between the groups, and a possible center effect should also be considered. In addition, only mild and moderate chronic graft‐versus‐host disease (GVHD) was associated with significantly improved survival compared to those without chronic GVHD in multivariate analysis. Thus, our results show that both unmanipulated haplo‐HSCT and UCBT are valid for high‐risk ALL children lacking a HLA matched donor, and both strategies expand the donor pool for children in need. Abstract : What's New? For patients with acute lymphoblastic leukemia (ALL), blood‐forming stem cells can be an effective therapy. In this study, the authors asked whether children for whom a matching donor cannot be found might benefit from either haploidentical hematopoietic stem cell transplantation (haplo‐HSCT) or umbilical cord‐blood transplantation (UCBT). They found that both therapies improved two‐year survival, although restoration of mature white blood cells was significantly faster after haplo‐HSCT than after UCBT. These therapeutic strategies may thus increase the donor pool for high‐risk children with ALL.